Cigarette Sales Forecasting at Bali Jaya Store Using the Single Method Exponential Smoothing - I Ketut Andri Purna Wijaya; Andi Yusika Rangan; Muhammad Ibnu Saad (STMIK Widya Cipta Dharma, 2026)
This study aims to forecast cigarette sales at Toko Bali Jaya using the Single Exponential Smoothing method as a quantitative approach to support more effective inventory management. The problems faced are the unstructured sales recording process and the manual determination of stock levels, which leads to inaccuracy in inventory control and potentially leads to overstocking or understocking. The Single Exponential Smoothing method was chosen because it is known to be effective in forecasting time series with fluctuating data patterns and no significant trends. The data used are cigarette sales data for 12 months which are processed to produce forecast values for the following period. The accuracy evaluation process is carried out using the Mean Absolute Percentage Error (MAPE) as an indicator of the level of forecast error. The results show that the best smoothing constant value is obtained at α = 0.3 with a MAPE value of 5.93%. This value indicates a low error rate, so the method used is able to produce forecasts that are close to the actual data. Thus, this method can be used as a basis for decision-making related to cigarette inventory management in a more systematic and measurable manner.